Slang Words on Rampage Movie - Tursini, Umi; Fauziah, Puja Isnatu (Actual Insight, 2022)
Language is divided into two, namely standard language and non-standard language. Slang is one of examples of non-standard language. Slangs means the use of informal words that are considered non-standard language. Slang usually found in movie, therefore slang and movie are related each other. This research aimed to identify slangs words used on Rampage movie. This study used the theory from Coleman (2012). The research was conducted using qualitative method. For the triangulation the researcher used investigator triangulation by discussing the findings with a lecturer who was expert in this subject. The findings of this study were: (1) English slangs created by changing meaning were 17 slangs; (2) English slangs created by changing in function were two slangs; (3) English slangs created by changing in form were seven slangs; (4) English slangs created by abbreviation was one slang; (5) English slangs made by changing spelling were three slangs; (6) English slangs created by language loans were two slangs. This study suggests the lecturer to use the findings as the option of effective authentic material. It is hoped that this research can help the students and English education in analyzing slangs word. This thesis can also be used as a reference for further researcher to analyze a movie more deeply.